Modeling and characterization of viscoelastic origami structures using a temperature variation-based model. (1st April 2021) - Kshad, Mohamed Ali E.; Naguib, Hani E.
Highlights: Using a general platform to model polymeric origami cores in sandwich structures. Considering viscoelastic properties of the base material at elevated temperatures. Using periodic boundary conditions in the shared edges of the repeated unit cells. Investigating the multi-unit cell origami panel based on the viscoelastic model. Abstract: The use of origami cores in sandwich structures is attracting increasing attention in many engineering applications due to origami cores' good compromise between weight and strength and their ability to dissipate energy. Modeling is one of the best tools for estimating design parameters for high performance. The primary outcome of this investigation is a general platform for modeling polymeric origami cores that takes into account the viscoelastic properties of the base material at elevated temperatures and periodic boundary conditions. The model considers a single origami unit cell as a representative unit element, which consists of repeating elements of the origami structure. Periodic boundary conditions were applied in the shared edges of the repeated unit cells. Furthermore, the work shows the results of multi-unit cell origami panel using the viscoelastic model.